Perceived Effects of Port and Harbor Accidents on Its Operational Performance: A Case Study of Apapa Seaport, Lagos State, Nigeria - O. J. Anyanwu; V. Omoke; C. T. Nwachukwu; O. C. Okorefe (Journal of Applied Sciences and Environmental Management)
The objective of this study was to evaluate the perceived effects of port and harbor accidents on its operational performance at the Apapa Seaport, Lagos State, Nigeria using eighty (80) questionnaires which were appropriately distributed out of which seventy-five (75) were accurately filled and returned. The study revealed that the majority of these accidents were caused by human error, equipment failure, and poor maintenance. The high rate of accidents at the Nigeria seaports has a significant effect on its operational performance and the study therefore recommends that near miss cases of accidents which contributes to more than 50% of total accidents in the port should be avoided including other recommendations.